2014
DOI: 10.1111/tri.12381
|View full text |Cite
|
Sign up to set email alerts
|

Blood dendritic cell levels associated with impaired IL-12 production and T-cell deficiency in patients with kidney disease: implications for post-transplant viral infections

Abstract: Summary Reduced pretransplant blood myeloid dendritic cell (mDC) levels are associated with post-transplant BK viremia and cytomegalovirus (CMV) disease after kidney transplantation. To elucidate potential mechanisms by which mDC levels might influence these outcomes, we studied the association of mDC levels with mDC IL- 12 production and T-cell level/function. Peripheral blood (PB) was studied in three groups: (i) end stage renal disease patients on hemodialysis (HD; n = 81); (ii) chronic kidney disease stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…After correction for 90% cell recovery, the average cell concentrations we found in healthy volunteers for different immune cell subsets were as follows: 1780 (1278-2,849) PBMCs; 1,156 (508-2013) lymphocytes; 310 (172-620) total monocytes; 101 (57-202) B-cells; 154 (51-202) NK-cells; 6.9 (2.2-18.4) mDCs; and 6.2 (2.7-10) pDCs per μl blood. These values are in concordance with values reported by other investigators (37)(38)(39). Although the normal range for concentrations of immune cell subsets has been reported by many investigators, there is debate regarding both the percentage and the absolute numbers of cells constituting this range.…”
Section: Biological Variation Of Pd-1 In Healthy Volunteerssupporting
confidence: 92%
See 1 more Smart Citation
“…After correction for 90% cell recovery, the average cell concentrations we found in healthy volunteers for different immune cell subsets were as follows: 1780 (1278-2,849) PBMCs; 1,156 (508-2013) lymphocytes; 310 (172-620) total monocytes; 101 (57-202) B-cells; 154 (51-202) NK-cells; 6.9 (2.2-18.4) mDCs; and 6.2 (2.7-10) pDCs per μl blood. These values are in concordance with values reported by other investigators (37)(38)(39). Although the normal range for concentrations of immune cell subsets has been reported by many investigators, there is debate regarding both the percentage and the absolute numbers of cells constituting this range.…”
Section: Biological Variation Of Pd-1 In Healthy Volunteerssupporting
confidence: 92%
“…Brahmer et al used background controls containing human IgG 4 isotype Table 1C. These values are in concordance with values reported by other investigators (37)(38)(39). Others have reported that using isotype antibodies can give erroneous results, and have shown that adequate blocking of non-specific antibody interactions and using directly conjugated antibodies can most often prevent the use of isotypes in flow cytometry (36).…”
Section: Discussionsupporting
confidence: 75%
“…For our functional studies, we used MoDCs as a substitute for mDCs in an in vitro model [12, 13, 17]. Six to Seven days are usually needed for monocytes to fully differentiate into mDCs in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…Monocyte-derived dendritic cells (MoDCs) were generated as previously described and used as an in vitro model for mDCs for additional functional studies [12, 13]. Briefly, monocytes were isolated from mononuclear cell fractions of the peripheral blood of healthy controls and seeded in the presence of GM-CSF (40 ng/ml; R&D systems, Minneapolis, MN) and IL-4 (20 ng/ml; R&D Systems) at a concentration of 1 × 10 6 cells/well in a 6-well plate.…”
Section: Methodsmentioning
confidence: 99%
“…[68] Therefore, monitoring the CMV-specific cellular immunity has been investigated to better predict the risk of CMV infection among recipients. [9] In general, the most commonly used diagnostic tools based on the principle of CMV-specific cellular immunity include CMV enzyme-linked immunospot (ELISPOT) assays and QuantiFERON-CMV test. The T-cell immune activity of former one could be measured by assessing the interferon-gamma (IFN-γ) production after the stimulation with CMV antigens such as phosphoprotein 65 (pp65) and immediate early 1 (IE-1), whereas the latter one is an enzyme-linked immunosorbent assay (ELISA) tool to test the released levels of IFN-γ in the whole blood by ex vivo stimulation with human leukocyte antigen (HLA) class I-restricted CMV peptides.…”
Section: Introductionmentioning
confidence: 99%